Keragaan Pertumbuhan dan Produksi Beberapa Aksesi Kacang Tunggak (Vigna unguiculata (L) Walp) di Desa Watidal Kabupaten Maluku Tenggara Barat - Gustaf K. Afitu; Helen Hetharie; Edyzon Jambormias (JURNAL BUDIDAYA PERTANIAN, 2016)
Cowpea (Vigna unguiculata (L) Walp) of the District of West Southeast Maluku (MTB) needs to be evaluated in the region of its origin. The objectives this research was to study the growth patterns of cowpea, to obtain local cowpea accessions with agronomic traits as expected, as well as high production potential. This research was conducted at Watidal village, MTB District, Maluku using a randomized completely block design (RCBD) with three replications. Factors to be tested was 15 accessions of cowpea. The observed variables were some vegetative characters, yield component and yield. Measured data were analyzed of its variance, and if the effects of treatments were highly significant then it is followed by Duncan difference test. The results showed differences in plant growth patterns, number of leaves, and number of internodes between accessions at 8 weeks after planting, and apparent at week 16. At week 16, most accessions showed a slowdown in growth rates including improved varieties (KT6). The result of variance test shows that the variation of plant height is significantly different, so that the variables of leaves number of branches, and all different variables are very real. Duncan's different test results show the appearance of lush growth through the number of leaves, the number of books and the number of branches more in accession KTm7, KTm27, KTm9, and KTm4, while some other local accessions including superior varieties showed a slight growth of leaf number. The results showed six accessions of KTm24, KTm13, KTm14, KTm12, KTm9, and KTm5 had the highest seed weight of the crop. Three accessions of local cowpea KTm5, KTm12 and KTm9 had the highest production components by weight of pod (g) and number of first pods.